THE INFLUENCE OF DEEP BREATH RELAXATION TECHNIQUE ON REDUCING PAIN INTENSITY IN POST-SECTIO CAESAREA WOMEN IN RSUD DR. DARSONO, PACITAN DISTRICT - Dwi Nurjayanti; Siti Nur Haliza (Jurnal Delima Harapan, 2023)
Post sectio caesarea (SC) pain is often a complaint for post SC mothers and often becomes an obstacle for the mobilization process and breastfeeding for newborns because mothers feel uncomfortable with the pain it causes. Medical efforts taken to reduce pain can be pharmacological and non-pharmacological. One of the non-pharmacological actions that help reduce pain is deep breathing relaxation techniques. This study aims to determine the effect of deep breathing relaxation techniques on reducing pain intensity in post SC mothers at Dr Darsono Hospital, Pacitan Regency. The research design used in this study was a pre and post test with a purposive sampling approach. This study used 2 variables, namely deep breathing relaxation technique as the independent variable and pain intensity as the dependent variable. Data from the research results will be analyzed using the Paired T-test statistic to determine the decrease in pain intensity before and after deep breathing relaxation techniques are performed. The results of the study showed that the majority of respondents experienced mild pain, 24 respondents (85.7%) and 4 respondents felt no pain (14.3%). Based on the results of the Paired T-test, it shows a significance value (p sign = 0.000) which means p sign <0.05. The conclusion of this study is that there is an effect of deep breathing relaxation techniques on reducing pain intensity in postoperative sectio caesarea mothers in the Flamboyan Room of RSUD dr. Darsono, Pacitan Regency.